2020
DOI: 10.1042/bsr20193130
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes predicts adverse cardiovascular outcomes after percutaneous coronary intervention: a meta-analysis

Abstract: Background: Prediabetes has been related with increased risk of coronary artery disease (CAD). However, the prognostic efficacy of prediabetes for patients receiving percutaneous coronary intervention (PCI) remains undetermined. We aimed to quantitatively evaluate the influence of diabetes on the risks of major adverse cardiovascular events (MACEs) after PCI in a meta-analysis. Methods: Longitudinal follow-up studies evaluating the association between prediabetes and risks of MACEs and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Out of the 4807 identified articles, 126 full-texts were assessed for eligibility, and finally, 16 articles were included in this umbrella review (Fig. 1) [7][8][9][10][23][24][25][26][27][28][29][30][31][32][33][34]. A detailed list of the excluded articles and the reasons for their exclusion is displayed in ESM Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 4807 identified articles, 126 full-texts were assessed for eligibility, and finally, 16 articles were included in this umbrella review (Fig. 1) [7][8][9][10][23][24][25][26][27][28][29][30][31][32][33][34]. A detailed list of the excluded articles and the reasons for their exclusion is displayed in ESM Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the results of prospective studies can serve as indirect evidence in favor of the adverse effect of prediabetes on the state of both the arterial wall as a whole and the severity of atherosclerotic changes in it [ 31 , 32 , 33 ]. So, in a recent national cohort study in Korea, with a 12-year prospective observation, it was shown that the DM group showed the highest incidence and risk of vascular complications (cardiovascular, renal; and retinal), followed by the IFG group and the lowest risk was in group of normoglycemia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of longitudinal follow-up studies, it was found that compared with patients with normoglycemia, coronary artery disease (CAD) patients with prediabetes on admission have a significantly higher risk of developing major adverse cardiovascular events after percutaneous coronary intervention (PCI). The potential prognostic role of prediabetes in these patients is the same regardless of study design, sample size, CAD subtype, PCI type, diabetes definition or follow-up duration, and even after adjusting for CAD severity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in figure 2, systematic reviews of observational studies have reported associations between different markers of disturbances in the glucose and insulin metabolism with CVD. Glycemic variability (34) was associated with poorer prognosis in coronary artery disease; fasting glucose (35) with higher risk of major cardiovascular adverse events (36)(37)(38) ; fasting insulin (39,40) with coronary artery disease, but there was no significant association between HOMA-IR (41) and stroke. Ultimately, an increase in C-peptide levels was associated with a rise in CVD mortality (42) .…”
Section: Diabetes and Disturbances In The Glucose And Insulin Metabolismmentioning
confidence: 92%
“…Most of the systematic reviews and meta-analyses on this topic were based on observational study designs, and therefore were prone to residual confounding that may affect the associations between diabetes and risk of cardiovascular disease. Furthermore, significant heterogeneity across studies attributable to variability in the measurement of outcomes and adjustment for covariates (34,35,44,45,48,(51)(52)(53) , subgroup comparisons (54), and duration of follow-up (34,55) , misclassification of diabetic cases (36,45,56) , as well as inconsistencies in defining conventional CVD risk factors (51,52) were observed. Publication bias was found in some of the systematic reviews (34,55,56) , and the limited availability of data and/or studies prevented further use of meta-regression analysis (45,51) .…”
Section: Diabetes and Disturbances In The Glucose And Insulin Metabolismmentioning
confidence: 99%